角化囊胞性歯原性腫瘍と正角化性歯原性囊胞における サイトケラチンの発現 - 林, 輝嘉; 井関, 富雄; 辻, 要; 森田, 章介; 松田, 彩起子; 田中, 昭男; 松島, 由紀; 和唐, 雅博; 山田, 耕治; 吉田, 博昭 (日本口腔外科学会雑誌, 2011)
Purpose. Lining epithelium of odontogenic keratocysts is classified into parakeratosis and orthokeratosis. The WHO classified odontogenic keratocysts with parakeratosis as keratocystic odontogenic tumors （KCOT） in 2005. In addition, odontogenic keratocysts with orthokeratosis were not classified as odontogenic tumors,although they are also referred to as orthokeratinized odontogenic cysts （OOC）. To clarify differences between these two lesions, we investigated their biological characteristics by immunohistochemical studies of cytokeratin （CK） in KCOT and OOC. Materials and Methods. We studied 15 cases of KCOT and 8 cases of OOC diagnosed according to the new WHO classification of 2005 at Osaka Dental University Hospital. We examined the immunohistochemical expression of CK10, 13, 17, and 19. To evaluate immunohistochemical staining, we divided the lining epithelium of these lesions into three layers（keratin layer, spinous layer, basal layer）, and we evaluated staining according to three levels: （−）, less than 10 ％ positive cells in each layer; （＋）, 10-50 ％ positive cells in each layer; and （＋＋）, more than 50 ％ positive cells in each layer. Results. 1） In KCOT, only 3 keratin layers were（＋）for CK10. 7 keratin layers and 12 sinous layers were （＋）, and 8 keratin layers and 12 spinous layers were（＋＋）for CK13. 12 keratin layers and spinous layers were （＋）, and 3 keratin layers and spinous layers were（＋＋）for CK17. 10 keratin layers were（＋）and 5 keratin layers were（＋＋）, and all spinous layers were（＋）and 6 basal layers were（＋）for CK19. 2）In OOC, 4 keratin layers and 3 spinous layers were（＋）, and 4 keratin layers and 5 spinous layers were（＋＋）for CK10. All cases were（−）for CK13 and CK17. All keratin layers and spinous layers were（−）, and 5 basal layers were （＋）for CK19. As for the expression of CK10, 13, 17, and 19, there were significant differences in the keratin layer or spinous layer between KCOT and OOC. Conclusions. There were differences in the expression of CKs between the lining epithelium of KCOT and that of OOC. These results provide evidence that KCOT has tumor-like characteristics.